Screening for silver resistant silE gene in Klebsiella pneumoniae isolated from wound and burn patients - Rahman, Jakia (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirement for the degree of B.Sc. in Microbiology, 2017.